Efeito da seleção para características de produção sobre qualidade espermática de duas linhagens paternas de suínos - Borges, Ana Claudia (2012)
Were evaluated the production of semen from 10 Large White boars and 10 fast-growing hybrid Duroc x Pietrain, averaging 18 months of age, males held as terminators in a artificial insemination center with different objectives of selection: the first used to improve the performance capacity and another lineage, increasing the quantity and quality of carcass meat. Data on semen parameters of 249 samples were analyzed using analysis of variance in a randomized block desigin and using Tukey (5% significance) tests and Wilcoxon (according to the data distribution) did not show statistical differences between the quantitative and morphological semen of boars, concluding that hybrid boars may have semen production as high as pets pure breed selected for rapid growth.